Anticoagulation in COVID-19: a review of current literature and guidelines. Issue 5 (20th October 2021) - Narasimhan, Bharat; Lorente-Ros, Marta; Aguilar-Gallardo, Jose S.; Lizardo, Christopher Perez; Narasimhan, Harish; Morton, Celia; Donahue, Kevin R.; Aronow, Wilbert S.
ABSTRACT: Severe acute respiratory syndrome coronavirus 2 infections are associated with greater risk of both arterial and venous thromboembolic events. Pathophysiology and Clinical implications: This has been attributed to a florid proinflammatory state resulting in microvascular dysfunction, activation of platelets and procoagulant systems as well as possible direct endothelial injury. The associated morbidity and mortality of these events has prompted much speculation and varied anticoagulation and fibrinolytic strategies based on multiple criteria including disease severity and biomarkers. No clear definitive benefit has been established with these approaches, which have frequently led to greater bleeding complications without significant mortality benefit. Overview: In this review, we outline the burden of these thromboembolic events in coronavirus disease-2019 (COVID-19) as well as the hypothesized contributory biological mechanisms. Finally, we provide a brief overview of the major clinical studies on the topic, and end with a summary of major societal guideline recommendations on anticoagulation in COVID-19.